COVID-19 Survivor Patients Carrying the Rs35705950 Risk Allele in MUC5B Have Higher Plasma Levels of Mucin 5B - Salvador García-Carmona; Ramcés Falfán-Valencia; Abigail Verónica-Aguilar; Ivette Buendía-Roldán; Leslie Chávez-Galán; Rafael de Jesús Hernández-Zenteno; Alfonso Martínez-Morales; Ingrid Fricke-Galindo; Jesús Alanis-Ponce; Daniela Valencia-Pérez Rea; Ilse Adriana Gutiérrez-Pérez; Oscar Zaragoza-García; et al. (Current Issues in Molecular Biology, 2022)
Background: Genetic susceptibility to infectious diseases is partly due to the variation in the human genome, and COVID-19 is not the exception. This study aimed to identify whether risk alleles of known genes linked with emphysema (SERPINA1) and pulmonary fibrosis (MUC5B) are associated with severe COVID-19, and whether plasma mucin 5B differs according to patients’ outcomes. Materials and methods: We included 1258 Mexican subjects diagnosed with COVID-19. We genotyped rs2892474 and rs17580 of the SERPINA1 gene and rs35705950 of MUC5B. Based on the rs35705950 genotypes, mucin 5B plasma protein levels were quantified. Results: Homozygous for the risk alleles of the three polymorphisms were found in less than 5% of the study population, but no statistically significant difference in the genotype or allele association analysis. At the protein level, non-survivors carrying one or two copies of the risk allele rs35705950 in MUC5B (GT + TT) had lower levels of mucin 5B compared to the survivors (0.0 vs. 0.17 ng/mL, p = 0.0013). Conclusion: The polymorphisms rs28929474 and rs17580 of SERPINA1 and rs35705950 of MUC5B are not associated with the risk of severe COVID-19 in the Mexican population. COVID-19 survivor patients bearing one or two copies of the rs35705950 risk allele have higher plasma levels of mucin 5B.